Interest in Revisiting Yogyakarta City Among Generation Z - Fitri Nur Hafidzah; Ilsya Hayadi (UNIVED Press, 2024)
This research aims to examine the influence of E-WoM, quality of experience, and destination image on revisit intention through tourist satisfaction in the city of Yogyakarta. The data used in this research is primary data. This research is included in quantitative research with a purposive sampling technique. The population of this study was 203 tourists who had visited the city of Yogyakarta in Indonesia. This research uses SEM-PLS version 4.0. The results of this research show that the experience quality and destination image have a significant positive effect on tourist satisfaction and revisit intention. Then the experience quality and destination image also have a significant positive effect on revisit intention through tourist satisfaction. Meanwhile, E-WoM has an insignificant positive effect on tourist satisfaction and an insignificant negative effect on revisit intention. E-WoM also has a positive and insignificant effect on intention to revisit through tourist satisfaction.